Estructura genetica de las poblaciones cultivadas de Lupinus albus L. - Lopez, R.=700 1 Moreno, M.T.; Suso, M.J.; Martin, L.M.
(Es, En)
ilus., 25 ref.
Keywords: LUPINUS ALBUS; ENDOGAMIA; ESTRUCTURA DE LA POBLACION; ESPAÑA; ALTRAMUZ